Challenges and Opportunities of E-Commerce in India - Amit Anand (International Journal of Scientific Multidisciplinary Research, 2023)
E-Commerce is a means of conducting business using one of the many electronic methods, usually involving telephones, computers or both. In other words it is about doing business using the technology. Everyday millions of transaction are conducted via the web, all of which fall under the E- Commerce. E-Commerce is about setting the business on the internet, allowing visitors to access the website and go through virtual catalogue of the product and service online. When the visitors want to buy something he or she can add it to their virtual shopping basket. Once all the information is entered, the buying and selling procedure is complete then the customer has to just wait for delivery. Currently there are 05 largest and most famous worldwide internet ratailers: Amazon, Dell, Flip kart, Snap deal and India Mart. With regard to Indian online market this study intends to explore the present situation of E-Commerce in India. It also shows the challenges and opportunities of E-Commerce in India in the prespective of the growing Global Economy. This article contains the secondary data for collection information. The place of the growth of E-commerce in india is satisfactory but slower in camparison to China and the USA. This article axplores the some opportunities which india has already adopted through modern ICTs 4G technologies, available broadband and so many local e-commerce business. But india still faces some basic problems like poor telecom infrastructure no strict legal bans, lack of good attitude towards fast growing technologies and stale academic syllabi regarding e-commerce